Criminal Law Enforcement Analysis Against Perpetrators of Illegal Lottery Gambling (Togel) in Parung Panjang District, Bogor Regency (A Study of Court Decision Number 257/Pid.B/2022/PN Cbi) - Sipahutar, Muhammad Saut; Hartini, Sri; Lestari, Nisa (Universitas Ibn Khaldun Bogor, 2025)
This study analyzes the enforcement of criminal law against offenders of illegal lottery gambling (togel) in Parung Panjang District, Bogor Regency, based on an evaluation of Court Decision Number 257/Pid.B/2022/PN Cbi. Togel is a form of illegal gambling that is widespread and has become a central focus of law enforcement efforts. The study emphasizes the legal enforcement process against togel offenders, encompassing the stages of investigation and inquiry by the police, prosecution by the public prosecutor, and judicial proceedings at the district court level. The findings indicate that the enforcement of the law against togel offenders has been carried out in accordance with existing legal provisions, including the application of the Indonesian Criminal Procedure Code (KUHAP) and other gambling-related legislation. The police serve as the frontline institution responsible for receiving public reports, conducting investigations, and identifying suspects involved in togel activities. The prosecution ensures the completeness of all case documents and forwards the matter to the court for trial. The judges, in turn, evaluate the legal facts and available evidence before rendering a verdict on the criminal offense. The study further reveals that, in adjudicating illegal lottery gambling cases, judges consider physical evidence, witness testimonies, the defendant’s confession, and both aggravating and mitigating circumstances. The principles of justice, proportionality, and humanity serve as fundamental foundations in the judicial process for prosecuting togel offenders.